2021
DOI: 10.1111/jbi.14076
|View full text |Cite
|
Sign up to set email alerts
|

Mountains, climate and niche heterogeneity explain global patterns of fern diversity

Abstract: Aim: It is well known that the distribution of species diversity is spatially heterogeneous, but understanding the factors contributing to this heterogeneity and to the formation of biodiversity hotspots remains a challenge. Here, we seek to improve our understanding of how historical, ecological and evolutionary processes contribute to current patterns of global fern diversity.Location: Worldwide. Taxon: Ferns.Methods: To evaluate the drivers of global fern diversity, we integrate over 800,000 georeferenced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 88 publications
3
63
0
Order By: Relevance
“…In an article by Suissa et al. (2021) , the authors analyzed species occurrence data downloaded from the Global Biodiversity Information Facility (GBIF) to address several questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an article by Suissa et al. (2021) , the authors analyzed species occurrence data downloaded from the Global Biodiversity Information Facility (GBIF) to address several questions.…”
Section: Introductionmentioning
confidence: 99%
“…(2018 , 2021b) , the completeness of the fern species lists for the 100 km × 100 km grid cells used in their study are likely very low, at least in some regions. Suissa et al. (2021) pointed out that “misidentified records or those with problematic localities can bias biodiversity analyses”, but they overlooked the problem of using substantially incomplete species lists in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified temperature, water availability (Bickford and Laffan, 2006; Qian et al, 2012), or a combination of these (Nagalingum et al, 2015; Link-Pérez and Laffan, 2018; Qian et al, 2021) to be important drivers of spatial fern diversity. A hump-shaped pattern of richness along elevation (maximum richness at intermediate elevations) has been frequently observed in ferns on mountains in tropical or sub-tropical areas (Kessler et al, 2011; Suissa et al, 2021). Hypotheses to explain such a pattern include purely geometrical constraints as well as biological hypothesis positing maximally favorable environmental conditions at mid-elevations (Colwell et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We further cleaned the list prior to analysis by filtering out any occurrences not within the second-degree mesh and removing duplicate collections (300,685 specimens, 673 taxa after filtering). Given the high quality of our occurrence data and the fact that automated occurrence cleaning algorithms ( eg , CoordinateCleaner; Zizka et al, 2019) have the potential to erroneously exclude true occurrence points ( ie , false positives; Zizka et al, 2020), we chose not to apply additional automated cleaning steps to our data as is often done with occurrence records obtained from GBIF ( eg , Rice et al, 2019; Suissa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, ferns and lycophytes are most diverse in mountains especially at lower latitudes, where the high environmental heterogeneity harbor a disproportionate number of species (Suissa, Sundue & Testo, 2021), reinforcing the importance of mountains in maintaining tropical fern diversity (Suissa & Sundue, 2020). Particularly, humid forests provide a suitable environment for high abundances and richness of fern and lycophyte species, where these organisms are able to develop in a wide range of biological forms (Senna & Waechter, 1997).…”
Section: Introductionmentioning
confidence: 99%